2020
DOI: 10.1111/1750-3841.15108
|View full text |Cite
|
Sign up to set email alerts
|

Degradations of aroma characteristics and changes of aroma related compounds, PPO activity, and antioxidant capacity in sugarcane juice during thermal process

Abstract: Alterations of aroma properties and aroma-related attributes of sugarcane juice during thermal processing under different temperatures (90, 100, and 110 • C) and treating time (10 s, 20 s, and 30 s) were assessed in this study. Changes in the volatility of aroma compounds were extremely complicated and respected to thermal processing conditions. Fructose, serine, and glutanic acid of sugarcane juice were increased at first and decreased at the end of treatment at high temperature. Phenolic compounds and PPO ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…When fresh noodles were stored at 25°C, the PPO activity of NT noodles increased within 12 hr; however, the PPO activity in the noodles of P-HT and U-HT showed a fluctuating change, but the overall trend was decreased, indicating that heat treatment could effectively passivate PPO in the noodles, but not completely. Similar results were obtained by Wang et al (2020), who found that the inhibition of PPO was intensified when the heating temperature or treating time was increased. At 4°C, the PPO activity of NT and heat-treated noodles was significantly decreased, among which the changes in NT fresh noodles were the most significant.…”
Section: Ppo Activity and Total Polyphenols Contentsupporting
confidence: 87%
“…When fresh noodles were stored at 25°C, the PPO activity of NT noodles increased within 12 hr; however, the PPO activity in the noodles of P-HT and U-HT showed a fluctuating change, but the overall trend was decreased, indicating that heat treatment could effectively passivate PPO in the noodles, but not completely. Similar results were obtained by Wang et al (2020), who found that the inhibition of PPO was intensified when the heating temperature or treating time was increased. At 4°C, the PPO activity of NT and heat-treated noodles was significantly decreased, among which the changes in NT fresh noodles were the most significant.…”
Section: Ppo Activity and Total Polyphenols Contentsupporting
confidence: 87%
“…Regarding total sugar content, this reduction was less than 8% and did not affect the soluble solids content ( Table 1 ). Wang et al [ 30 ] evaluated quality changes of sugarcane juice after thermal treatments under different temperatures (90, 100, and 110 °C) and processing time (10, 20, and 30 s). The authors observed an increase of glucose content, whereas a sucrose content reduction was verified for all temperatures and processing time as well as their combinations.…”
Section: Resultsmentioning
confidence: 99%
“…At the initial stage, 3-ethyl-2-methyl-1,3-hexadiene had the highest concentration (2.29 µg/g) and went down to zero at S-90. However, the hydrocarbons identified in fresh cane juice were not classified as an aroma component as they have high odor threshold values [ 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the initial stage, 3-ethyl-2-methyl-1,3-hexadiene had the highest concentration (2.29 µg/g) and went down to zero at S-90. However, the hydrocarbons identified in fresh cane juice were not classified as an aroma component as they have high odor threshold values [13,14]. D-limonene was the only terpene hydrocarbon that was detected throughout the heating and dehydration process, except in S-180, and was present in the final product (S-240, 0.2 µg/g), presenting a floral-like odor contribution to the NCS aroma.…”
Section: Changes In the Concentration Profiles Of Hydrocarbons And Terpene Hydrocarbonsmentioning
confidence: 99%
See 1 more Smart Citation